Reading Trilce like reading Rayuela - González Montes, Antonio (2022)
In the following pages, we propose to approach, in part, the poetic world of the book Trilce (1922), by César Vallejo. We will concentrate on the exegesis of two poems of the aforementioned volume: «II» and «V», which are exemplary expressions of Vallejo's great vision of temporality and the love relationship. The title of the article is intended to emphasize the need to read with freedom, which is why we have established a special relationship between Trilce and Rayuela, since we understand that these two books demand an active, participatory, and creative reader.